Analisis Penggunaan Aplikasi Smart Port E-Logistic (Mycargoo) pada PT PELNI (Persero) Cabang Jayapura - Adhar Dwi Irjanto; M. Ikhsan F (Indonesian Maritime Researchers and Lecturers, 2025)
The formulation of the problem of this study is: 1) The number of customers who use the MyCargoo application is still small or the ordering process is still mostly done offline. 2) The high number of complaints from customers who use the MyCargoo application. The objectives of this study are 1) To describe the implementation of MyCargoo at PT Pelni (Persero) Jayapura Branch, 2) To describe the obstacles to using MyCargoo at PT Pelni (Persero) Jayapura Branch. The research method used is descriptive qualitative research. This research was conducted at PT Pelni (Persero) for 3 months, starting from February 2023 to May 2023. The data collection techniques used were by observation, interviews, documentation, and literature studies. While the informants in this study were the staff of the cargo division of PT Pelni Jayapura Branch. The results of this study are the implementation of MyCargoo at PT Pelni (Persero) Jayapura Branch, there are 2 types, namely 1) Implementation of My Cargoo Application services at PT Pelni Jayapura Branch, namely: a.) According to the type of service, including: Door to door (Full Service), Door to port, Port to Door, Port to port. b.) According to the type of load, including: Dry Container, Cargo, Motor Vehicles, Redpack, Car Vehicles, Reefer Containers. 2) Constraints from the Use of MyCargoo at PT Pelni (Persero) Jayapura Branch, namely: a.) Unstable Network, Electrical Short Circuit, MyCargoo Features are Still Minimal, Low Public Knowledge.